2014
DOI: 10.4161/15384101.2014.967066
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of zygotic genome activation and DNA damage checkpoint acquisition at the mid-blastula transition

Abstract: Following fertilization, oviparous embryos undergo rapid, mostly transcriptionally silent cleavage divisions until the mid-blastula transition (MBT), when large-scale developmental changes occur, including zygotic genome activation (ZGA) and cell cycle remodeling, via lengthening and checkpoint acquisition. Despite their concomitant appearance, whether these changes are co-regulated is unclear. Three models have been proposed to account for the timing of (ZGA). One model implicates a threshold nuclear to cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 54 publications
(70 reference statements)
5
31
0
Order By: Relevance
“…Compromising this aspect of the normal gene expression program will almost certainly affect embryogenesis, consistent with mutations in cohesin causing the human developmental disorder Cornelia de Lange syndrome (CdLS). Although cell proliferation is central to early development, in Drosophila and zebrafish, ZGA is independent of, or upstream of, cell cycle number and checkpoint regulators (Blythe and Wieschaus, 2015;Zhang et al, 2014aZhang et al, , 2017. Consistent with these observations, we found that delay in ZGA occurred in Rad21depleted embryos that had the same number of cells as controls.…”
Section: Rad21 Depletion Delayed Zga and Dysregulated Transcripts In supporting
confidence: 86%
“…Compromising this aspect of the normal gene expression program will almost certainly affect embryogenesis, consistent with mutations in cohesin causing the human developmental disorder Cornelia de Lange syndrome (CdLS). Although cell proliferation is central to early development, in Drosophila and zebrafish, ZGA is independent of, or upstream of, cell cycle number and checkpoint regulators (Blythe and Wieschaus, 2015;Zhang et al, 2014aZhang et al, , 2017. Consistent with these observations, we found that delay in ZGA occurred in Rad21depleted embryos that had the same number of cells as controls.…”
Section: Rad21 Depletion Delayed Zga and Dysregulated Transcripts In supporting
confidence: 86%
“…This failure of α-amanitin to suppress the lethal phenotype of checkpoint-deficient embryos is also in agreement with results in Xenopus and zebrafish (Ikegami, Rivera-Bennetts, Brooker, & Yager, 1997;Newport & Dasso, 1989;Zhang, Kothari, Mullins, & Lampson, 2014) that showed no effect of α-amanitin on checkpoint-dependent S-phase lengthening at the MBT. Instead, the demonstrated link between checkpoint activation and the chromatin transition at the MBT highlights the need to identify the specific changes that occur in chromatin structure preceding the MBT, especially those that delineate euchromatic and heterochromatic regions and may have a major impact on checkpoint activation.…”
Section: Factors That Trigger the Dna Damage Response At The Mbtsupporting
confidence: 88%
“…Although cell proliferation is central to early development, in Drosophila and zebrafish, ZGA is independent of, or upstream of cell cycle number and checkpoint regulators (Blythe and Wieschaus, 2015; Zhang et al, 2014a; Zhang et al, 2017). Consistent with these observations, we found that delay in ZGA occurred in Rad21-depleted embryos that had the same number of cells as controls.…”
Section: Discussionmentioning
confidence: 99%